A' = {a, e, f, g, h, i, j, k, l, m, n, o, p q, r, s, t, u, v, w, x, y, z}
(everything except b, c, and d)
B' = {a, b, d, h, i, j, k, l, m, n, o, p q, r, s, t, u, v, w, x, y, z}
(everything except c, e, f, and g)
c) A′ ∩ B′ = {a, h, i, j, k, l, m, n, o, p q, r, s, t, u, v, w, x, y, z}
(everything except b, c, d intersected with everything except c, e, f, g produces everything except b, c, d, e, f, g)
d) A′ U B′ = {a, b, d, e, f, g, h, i, j, k, l, m, n, o, p q, r, s, t, u, v, w, x, y, z}
(everything except b, c, d unioned with everything except c, e, f, g produces everything except c)
e) A U B′ = {a, b, c, d, h, i, j, k, l, m, n, o, p q, r, s, t, u, v, w, x, y, z}
({b, c, d} unioned with everything except c, e, f, g produces everything except e, f, g)
f) (A U B′) ∩ B = {c}
(everything except e, f, g intersected with {c, e, f, g} produces only c)
g) (A U B) ∩ (A U B′) = A = {b, c, d}
({b, c, d, e, f, g} intersected with everything except e, f, g produces {b, c, d}, which is A.)
2007-01-19 08:43:34
·
answer #1
·
answered by Jim Burnell 6
·
0⤊
0⤋